Impact of child labor in stone quarries on his health status in El- Minia city - EL-Aty, Naglaa Saad Abd; EL-Ghany, Nazek Ibrahim Abd; Moftah, Farag Mohammed; Labeeb, Shokria Adly; Mohammed, Awatef Abdel-Razak (International Journal of Advanced Nursing Studies, 2016)
Background: Child labor today represents the largest single cause of child abuse across the global. Most of it takes place in economically less developed countries and much is hidden.Objectives: The aims of this study were to found out the nature and impact of child labor in the stone quarries on his health status and assess the work hazards associated with these concern.Methods Design: A descriptive comparative design was used .Setting: at stone quarries in El-Minia city and two Governmental schools (primary and preparatory).Sample: Study consisted sample of two groups: two hundred working children (studied group) and three hundred school children as control group.Tools: Three tools were developed and utilized. Socio-demographic characteristics, assessment sheet, and Observation check list.Results: It was found that the mean age studied group was 13.0Â± 1.2, compared to 12.0Â± 1.2for control group. More than half of studied group of studied group were working for the need to money and to share in family income. About two third of studied group exposed to different types of injuries during work in quarry. There was statistical significant difference between studied and control group groups regarding body mass index physical assessment and bad habits. Also the results of this study explored that most of studied group exposed to all items of work hazards.Conclusion: It can be concluded that almost all working children in stone quarries were facing much health complains and working hazards.Recommendations: Quarries owners should provide all working children with appropriate protective measures and trained them on methods of protecting themselves from work hazards.